Release of EPA and DHA from salmon oil – a comparison of in vitro digestion with human and porcine gastrointestinal enzymes - Aarak, K. E.; Kirkhus, B.; Holm, H.; Vogt, G.; Jacobsen, M.; Vegarud, G. E. (British journal of nutrition, 2013)
In the present study, we hypothesised whether in vitro digestion of salmon oil would release different amounts of PUFA depending on the origin of the lipolytic enzymes used. For this purpose, in vitro digestion of salmon oil (SO) was performed using human duodenal juice (HDJ) or a commercial enzyme preparation consisting of porcine pancreatin and bile (PB). The lipolytic effect was determined by measuring the release of fatty acids (FA) using solid-phase extraction and GC–flame ionisation detection, withdrawing samples every 20 min during digestion. The amount of FA released indicated that a plateau was reached after 80 min with approximately similar amounts of FA detected using both HDJ and PB (379 (sd 18) and 352 (sd 23) mg/g SO, respectively). However, the release of 18 : 2, EPA (20 : 5) and DHA (22 : 6) was significantly different during in vitro digestion. At 80 min, HDJ and PB released 43 and 33 % of 18 : 2, 14 and 9 % of EPA and 11 and 9 % of DHA, respectively. Both enzyme preparations released approximately the same amounts of the other FA analysed. The effect of the addition of bile salts (BS) was significantly different in the two enzyme systems, where porcine pancreatin highly responded to the increase in BS concentration, in contrast to HDJ.